P‐16: Implementation of TCAD Simulation of a‐IGZO Corbino TFTs for AMOLED Application. Issue 1 (May 2017) - Han, Ji-Ung; Lee, Won-Seok; Tak, Nam-Kyun; Choi, In-Chol; Kim, Jin-young; Hwang, Man-gyu; Geng, Di; Choe, Younwoo; Jang, Jin
Abstract : We studied the effects of Corbino structure amorphous indium‐galium‐zinc oxide (a‐IGZO) thin film transistors (TFTs) using TCAD and circuit simulator. The Corbino structure shows the special behavior with drain electrode in inner or outer. By simulation, we confirm the Corbino structure have better performance than conventional structure for AMOLED pixel circuit.